Elucidating the molecular mechanisms associated with TARS2-related mitochondrial disease. Issue 4 (11th September 2021) - Zheng, Wen-Qiang; Pedersen, Signe Vandal; Thompson, Kyle; Bellacchio, Emanuele; French, Courtney E; Munro, Benjamin; Pearson, Toni S; Vogt, Julie; Diodato, Daria; Diemer, Tue; Ernst, Anja; Horvath, Rita; et al.
Abstract: TARS2 encodes human mitochondrial threonyl tRNA-synthetase that is responsible for generating mitochondrial Thr-tRNA Thr and clearing mischarged Ser-tRNA Thr during mitochondrial translation. Pathogenic variants in TARS2 have hitherto been reported in a pair of siblings and an unrelated patient with an early onset mitochondrial encephalomyopathy and a combined respiratory chain enzyme deficiency in muscle. We here report five additional unrelated patients with TARS2 -related mitochondrial diseases, expanding the clinical phenotype to also include epilepsy, dystonia, hyperhidrosis and severe hearing impairment. In addition, we document seven novel TARS2 variants—one nonsense variant and six missense variants—that we demonstrate are pathogenic and causal of the disease presentation based on population frequency, homology modeling and functional studies that show the effects of the pathogenic variants on TARS2 stability and/or function.